RESISTEMATISASI DAN RESTRUKTURALISASI ILMU MA’ANI DALAM DESAIN PEMBELAJARAN ILMU BALAGHAH - Taufiqurrochman, R. (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
The development of semantics as part of Balaghah (Rhetoric) is necessary because of the fact that the semantics got less popularity and it is thought to be hard to learn. For this reason it is necessary to design the learning of ma’ani (semantics) that has orientation to the re-systematization and re-structuralization of the learning material. There is fundamental change in the system of rhetoric, that is placing the ma’ani at the beginning, followed by bayan and badi’. Ma’ani has to be presented easily because it is the gate for the balaghah. The position of Maani in the hierarchy of balaghah can not be separated from grammar that is familiar to be learnt by Indonesian students. The consequence of Ma’ani as the follow up of nahwu is the change of system of learning materials that differs the nahwu perspective and balaghah perspective. Eventually, rhetoric of Arabic language is not only used when analyzing the divine text such as Quran and Hadith but also literary works, poems, prose, advertising , journalism, and others. By having such application balaghah is expected to be more inclusive, not only for analyzing literary works but also for many other analysis, because the final aim of the balaghah is forming civilized people indicated by the ability of adapting oneself properly, beautifully, according to the situation and condition.